Trends in healthy life expectancy between 2002 and 2018 in Germany - Compression or expansion of health-related quality of life (HRQOL)?. (March 2021) - Klar, Marie Kristin; Geyer, Siegfried; Safieddine, Batoul; Tetzlaff, Fabian; Tetzlaff, Juliane; Sperlich, Stefanie
Abstract: The question of whether rising life expectancy has led to additional life years spent in good health or poor health is of major public health relevance. We tested the theories of compression or expansion of morbidity for Germany with respect to the mental and physical component summary scales (MCS/PCS) of the health-related quality of life (HRQOL) questionnaire (SF-12). Data of 90, 758 women and 81, 400 men were obtained from the German Socio-Economic Panel between 2002 and 2018. Linear and logistic regression analyses were applied to estimate temporal changes in MCS and PCS in different life stages. The development of healthy life expectancy (H-LE) expressed by life years without severe functional limitations was calculated by applying the Sullivan method. Overall, a significant increase of MCS and PCS was found in both genders. The rise was mainly due to declining proportions of severe limitations (norm values < 40 points) while the proportions of norm values > 60 points did not change substantially. Improvements were most apparent for the 'young seniors' (65–79 years) and at 'old age' (80 years +). In contrast, no improvements in PCS were found for 'later working life' (50–64 years) and decreasing levels were observed for persons of 'middle working age' (30–49 years). During the study period, H-LE at age 50 increased in women/men by 2.93/2.90 years (MCS) and 1.92/2.53 years (PCS), respectively. Our results support the hypothesis of absolute compression of morbidity. However, since consistent improvements were not found for ages below 65 years, it remains open to debate whether the positive health trend will also persist in the future. Our findings suggest that health promotion efforts should be strengthened for people of middle and later working age to support healthy aging. Highlights: In Germany, mental and physical quality of life increased between 2002 and 2018 for both genders. Overall, our findings pointing to absolute compression of morbidity. Improvements in health-related quality of life were most pronounced among people aging 65 years or older. Our results speak in favor of a life stage specific approach to the analysis of health trends.